Sebaran dan Karakter Morfologi Lebah Madu Hutan Apis dorsata (F.) di Pulau Sermata Kabupaten Maluku Barat Daya - Pattikawa, Romario Hendra; Lamerkabel, Jacobus S A; Hasinu, Jeffij V (Universitas Pattimura, 2023)
This study aims to determine the distribution and morphological characteristics of the forest bee (Apis dorsata F.) on Sermata Island, Southwest Maluku Regency. The research was conducted in Pupliora Village, Mahaleta Village, Rumkisar Village and Batu Gajah Village on Sermata Island from November to December 2021. The method used in this study was a survey methode on each nest of A. dorsata [F.] forest honeybees on Sermata Island. The results showed that the distribution of Apis dorsata F. forest honey bee hives found on Sermata Island was 51 active nest colonies and 37 inactive nests, at an altitude of 38-215 m asl, with nesting sites found, namely mango trees, breadfruit trees, banyan trees, salawaku trees and rock cliffs. For heights from the ground surface ranging from 4-29 m. The average size of the morphometric characters of Apis dorsata worker bees found was body length 2.0-2.2 cm, head width 0.4-0.5 cm, body length 2.0-2.2 cm, head width 0.4-0.5 cm, head 0.4-0.6 cm. Front wing length 1.3-1.4. The size of the hind wings is 0.9 cm, and the length of the hind legs is 1.1-1.2 cm.